Quality Control of Subtitles: A Study of Subtitlers, Proofreaders, Quality Controllers, LSPs and Broadcasters/Streaming Services - Nikolic, Kristijan (Journal of Audiovisual Translation, 2021)
Quality control of subtitles is a relatively unresearched field, even though it has a significant influence on the overall quality, and thus viewers’ experience of subtitles. It is carried out in different ways: various language service providers and broadcasters have different procedures, for instance, it sometimes solely involves proofreading. An online questionnaire has been distributed among professionals involved in the production chain of subtitles: broadcasters, streaming and video-on-demand services, vendors also known as language service providers, subtitlers, quality controllers and proofreaders. The hope is that this report will enable professionals involved in quality control of subtitles to further enhance their quality control procedures. The results of this research could also be used in experimental investigation of viewers’ perception of quality in subtitling by using the same research methods applied in this study. Lay Summary We do not know much about the quality control of subtitles on which many viewers depend to be able to follow TV content in foreign languages, or because they are deaf or hard-of-hearing. I conducted research by means of an online questionnaire among professionals and organisations involved in the production of subtitles to check how and whether they ensure viewers get subtitles of the highest possible quality. One of the main findings of the survey is that all professionals involved in the subtitling process think that the quality of subtitles is important, and that freelance subtitlers largely don’t think their clients pay enough attention to subtitling quality. The questionnaire was sent to TV and streaming broadcasters, agencies that work as intermediaries between broadcasters and subtitlers, quality controllers and proofreaders. Based on the findings of this survey, I have recommended several steps that can be taken to ensure better quality subtitles.